Exploring the Role of Spiritual Accounting in Enhancing Ethical Accountability in Nigeria’s Public Sector - Eteng, Confidence Onun; Essien, Joy Edeheudim; Essien, Edeheudim Elijah Essien (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examined the role of spiritual accounting in enhancing ethical accountability in Nigeria’s public sector, with particular emphasis on public servants in Keffi, Abuja, and Lafia. It sought to determine whether the integration of spiritual values into public service influences ethical decision-making, transparency, honesty, and accountability in the management of public resources. Methodology: The study adopted a mixed-method research approach using a descriptive survey design. Primary data were collected through structured questionnaires administered to 150 public sector employees selected from Keffi, Abuja, and Lafia. Data were analyzed using descriptive statistics, Pearson correlation, and regression analysis to examine the relationship between spiritual accounting and ethical accountability. Results: The findings revealed a statistically significant positive relationship between spiritual accounting and ethical accountability. Regression results showed that spiritual accounting explained 47.3% of the variation in ethical accountability, indicating that public officials who internalize spiritual values exhibit higher levels of transparency, integrity, honesty, and responsible stewardship of public resources. The study concludes that spiritual accounting provides a complementary ethical framework that strengthens conventional legal and institutional accountability mechanisms in the Nigerian public sector. Implication of Findings: The findings suggest that incorporating spiritual and moral values into public sector ethics through training programmes, value-based codes of conduct, and inclusive ethical awareness initiatives could reinforce integrity, improve accountability, and contribute to reducing corruption and unethical practices in public governance.